2015
DOI: 10.1039/c5ra11081e
|View full text |Cite
|
Sign up to set email alerts
|

Air-processed, efficient CH3NH3PbI3−xClx perovskite solar cells with organic polymer PTB7 as a hole-transport layer

Abstract: Low-temperature, solution-processed perovskite solar cells (PSCs), which utilized organic poly [4,8-bis[(2-ethylhexyl) [3,4-b]-thiophenediyl] (PTB7) as a hole-transport layer (HTL), achieved a power conversion efficiency (PCE) as high as 13.29% when fabricated in ambient air. Through a comparative study, we demonstrate this PCE value to be superior compared to its counterparts with Spiro-OMeTAD or P3HT as the HTL; the superiority consists in higher fill factor (FF) and open-circuit voltage (V oc ). By probing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
(66 reference statements)
1
23
0
Order By: Relevance
“…Improved PCEs also resulted from the addition of Li‐bis(trifluoromethanesulfonyl)‐imide (LiTFSI) dopants to the spiro‐MeOTAD, which substantially enhanced conductivity of the HTL . LiTFSI is a commonly employed dopant for many other HTLs such as Poly[bis(4‐phenyl)(2,4,6‐trimethylphenyl)amine] (PTAA),[1b], poly3hexylthiophene (P3HT), Poly[[(2,4‐dimethylphenyl)imino]‐1,4‐phenylene(6,12‐dihydro‐6,6,12,12‐tetraoctylindeno[1,2‐b]fluorene‐2,8‐diyl)‐1,4‐phenylene] (PIF8‐TAA), and Poly ({4,8‐bis[(2‐ethylhexyl)oxy]benzo [1,2‐ b :4,5‐ b ′]dithiophene‐2,6‐diyl}{3‐fluoro‐2‐[(ethylhexyl‐2)carbonyl]thieno[3,4‐ b ]thiophenediyl}) (PTB7) in perovskite solar cells. The top electrode and the spiro‐MeOTAD HTL beneath are usually the most affected by extrinsic environmental conditions (O 2 , H 2 O, N 2 , temperature, and light) .…”
Section: Extracted Hole Mobility Values Of As‐prepared Spiro‐meotad Fmentioning
confidence: 99%
“…Improved PCEs also resulted from the addition of Li‐bis(trifluoromethanesulfonyl)‐imide (LiTFSI) dopants to the spiro‐MeOTAD, which substantially enhanced conductivity of the HTL . LiTFSI is a commonly employed dopant for many other HTLs such as Poly[bis(4‐phenyl)(2,4,6‐trimethylphenyl)amine] (PTAA),[1b], poly3hexylthiophene (P3HT), Poly[[(2,4‐dimethylphenyl)imino]‐1,4‐phenylene(6,12‐dihydro‐6,6,12,12‐tetraoctylindeno[1,2‐b]fluorene‐2,8‐diyl)‐1,4‐phenylene] (PIF8‐TAA), and Poly ({4,8‐bis[(2‐ethylhexyl)oxy]benzo [1,2‐ b :4,5‐ b ′]dithiophene‐2,6‐diyl}{3‐fluoro‐2‐[(ethylhexyl‐2)carbonyl]thieno[3,4‐ b ]thiophenediyl}) (PTB7) in perovskite solar cells. The top electrode and the spiro‐MeOTAD HTL beneath are usually the most affected by extrinsic environmental conditions (O 2 , H 2 O, N 2 , temperature, and light) .…”
Section: Extracted Hole Mobility Values Of As‐prepared Spiro‐meotad Fmentioning
confidence: 99%
“…Du et al [ 100 ] employed PTB7 (a p-type materials used in organic photovoltaics (OPV)) as the HTL. Du et al [ 100 ] employed PTB7 (a p-type materials used in organic photovoltaics (OPV)) as the HTL.…”
Section: Hole Transport Materialsmentioning
confidence: 99%
“…Fullerene modifi cation on TiO 2 was fi rst reported to improve the device performance by facilitating charge extraction at the ETL interfaces. [ 100,171 ] Stability test results suggested that the stability of perovskite was effectively improved under ambient air. [ 170 ] Recently, Yang group [ 109 ] synthesized a triblock fullerene derivative (PCBB-2CN-2C8) to modify the surface of TiO 2 (Figure 16 c,d).…”
Section: Strategies To Protect Perovskite From Light Via Interface Momentioning
confidence: 99%
“…However, a different thiophene‐based donor polymer, PTB7 , demonstrated a remarkably better device efficiency of 13.29% ( J SC of 20.2 mA cm −2 , V OC of 0.94, and FF of 70%) after doping with Li‐TFSI and tBP and device optimization . PTB7 had three‐fold higher conductivity than P3HT (9.5 S/cm against 3.0 S cm −1 for P3HT) and almost five‐fold higher than conventional spiro‐OMeTAD (2.0 S cm −1 ).…”
Section: Hole Transport Materialsmentioning
confidence: 99%